1998
DOI: 10.1042/bj3340393
|View full text |Cite
|
Sign up to set email alerts
|

Selective loss of substrate recognition induced by the tumour-associated D294G point mutation in protein kinase Cα

Abstract: The tumour-associated D294G mutant of protein kinase Calpha (PKCalpha) was recently shown not to be translocated to the plasma membrane on stimulation with PMA, in contrast with the wild-type enzyme. Using recombinant wild-type and mutant PKCalpha, we establish here that, although the PKCalpha intrinsic lipid-dependent catalytic activity remains unaltered by the D294G mutation, the mutant enzyme exhibits a selective loss of substrate recognition. Indeed, whereas the mutant enzyme is still able to phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…1D). Thus, one of the major cell biological defects of the PKCa-D294G mutant is the loss of tight membrane binding even upon treatment of TPA, consistent with the proposition by others that this mutant may have reduced stability of membrane association (5,9).…”
Section: Resultssupporting
confidence: 64%
“…1D). Thus, one of the major cell biological defects of the PKCa-D294G mutant is the loss of tight membrane binding even upon treatment of TPA, consistent with the proposition by others that this mutant may have reduced stability of membrane association (5,9).…”
Section: Resultssupporting
confidence: 64%
“…Journal of Cell Science 117 (1) A cell-cell contact-induced signal responsible for the selectivity The D294G mutation induces a selective loss in the recognition of substrates exhibiting anchoring protein properties without affecting PKCα catalytic activity (Prevostel et al, 1998). This suggests that the selectivity of PKCα targeting to cellcell contacts might be mediated through protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the function of this region. In a previous study, we have established that the D294G mutation induces a selective loss in the recognition of substrates with properties of anchoring proteins (Prevostel et al, 1998). Recently, Parsons et al (Parsons et al, 2002) have identified a binding motif for β1 integrin within the PKCα V3 region that is critical for directed tumour cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…In GH3B6 cells, the fact that PKC␣ relocated to the cytoplasm before the [Ca 2ϩ ] i decreased to baseline levels (52) also indicates that cPKC activation is not always phase locked with variations in calcium concentration as suggested in many studies, such as that of Violin et al, who also showed the coincidence of PKC substrate phosphorylation with calcium oscillations (54). In addition, we have shown that the selective targeting of PKC␣ to cell-cell contacts is probably finely regulated at the molecular level, since the natural D294G point mutation (located in the V3 region of the enzyme and thus not involved in calcium or DAG binding), previously identified in human pituitary and thyroid tumors (2,40,41), abolished the selective accumulation of PKC␣ at the cell-cell contact (51). The same result was obtained when this mutation was introduced in the PKCε coding sequence (43).…”
mentioning
confidence: 85%